2012
DOI: 10.1124/jpet.112.196485
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Influence of the Hexapeptidic Sequence SLIGRL on Influenza A Virus Infection in Mice

Abstract: Proteinase-activated receptor 2 (PAR 2 ) is widely expressed in the respiratory tract and is an integral component of the host antimicrobial defense system. The principal aim of this study was to investigate the influence of a PAR 2 -activating peptide, SLIGRL, on influenza A virus (IAV)-induced pathogenesis in mice. Intranasal inoculation of BALB/c mice with influenza A/PR/8/34 virus caused time-dependent increases in the number of pulmonary leukocytes (recovered from bronchoalveolar lavage fluid), marked air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…45 However, a recent study showed that this peptide mediated PAR2-independent protection against IAV. 74 It is difficult to explain the different results found with IAV infection in PAR2ko mice ( Table 2). This could be due to differences in virus dose and virus preparation.…”
Section: Role Of Par2 In Iav Infection In Micementioning
confidence: 54%
“…45 However, a recent study showed that this peptide mediated PAR2-independent protection against IAV. 74 It is difficult to explain the different results found with IAV infection in PAR2ko mice ( Table 2). This could be due to differences in virus dose and virus preparation.…”
Section: Role Of Par2 In Iav Infection In Micementioning
confidence: 54%
“…Our laboratory has recently shown that the hexapeptidic sequence SLIGRL-amide (Ser-Leu-Ile-Gly-Arg-Leu-NH 2 ) inhibits IAV infection in mice [ 7 ]. SLIGRL-amide is a well-established activator of protease-activated receptor-2 (PAR-2) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLIGRL-amide is a well-established activator of protease-activated receptor-2 (PAR-2) [ 8 ]. However, SLIGRL-amide inhibits IAV infection independently of PAR-2 as anti-viral effects were preserved in PAR2 (−/−) mice [ 7 ]. SLIGRL-amide has also been reported to activate MRGPRC11, a subtype of MAS-related G protein-coupled receptor (MRGPR) [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PR8 virus was propagated in the allantoic fluid of 9-day old embryonated chicken eggs (Altona Hatchery, Forrestfield, Australia) at 37°C for 3 days and harvested as previously described [22], stored in single use aliquots at −80°C and diluted 1:100 to 1:400 in sterile PBS prior to intranasal vaccination of mice.…”
Section: Methodsmentioning
confidence: 99%